2020
DOI: 10.1371/journal.pone.0241551
|View full text |Cite
|
Sign up to set email alerts
|

MAGE-A3 is a prognostic biomarker for poor clinical outcome in cutaneous squamous cell carcinoma with perineural invasion via modulation of cell proliferation

Abstract: Perineural invasion is a pathologic process of neoplastic dissemination along and invading into the nerves. Perineural invasion is associated with aggressive disease and a greater likelihood of poor outcomes. In this study, 3 of 9 patients with cutaneous squamous cell carcinoma and perineural invasion exhibited poor clinical outcomes. Tumors from these patients expressed high levels of MAGE-A3, a cancer testis antigen that may contribute to key processes of tumor development. In addition to perineural invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Perineural invasion was present 34.3% of patients in our study, and varied widely in previous studies 25,26) . The study by Chen et al found that perineural invasion cutaneous squamous cell carcinoma was associated with increased MAGE-A3 expression 27) . The results of our study suggest that larger samples are required to interpret the role of perineural invasion in ACC.…”
Section: Discussionmentioning
confidence: 98%
“…Perineural invasion was present 34.3% of patients in our study, and varied widely in previous studies 25,26) . The study by Chen et al found that perineural invasion cutaneous squamous cell carcinoma was associated with increased MAGE-A3 expression 27) . The results of our study suggest that larger samples are required to interpret the role of perineural invasion in ACC.…”
Section: Discussionmentioning
confidence: 98%
“…Our transcriptomic analysis upon SIN3A-PF1 perturbation in 3D culture system showed significant alteration of several genes. Matrix metalloproteases proteins (MMP1 & MMP3) known enhancers of invasion and MAGEA3, CDH11, SPOCK, PTGS2 and WNT5A, overexpressed in high grade of invasive cancer, are all downregulated in PF1-SID cells [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] . LHX8 and its family member LHX6, known to inhibit breast cancer cell proliferation by repressing WNT signaling, is the topmost upregulated gene in PF1-SID cells [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, MAGE-A3 expression in cSCC correlates with poor prognosis. In a follow up study, MAGE-A3 was found to be enriched in poorly-differentiated tumors with perineural invasion (PNI) relative to moderately differentiated tumors [ 69 ]. In vitro human cSCC cell lines and in vivo mouse models were used to demonstrate that MAGE-A3 may govern cell cycle progression and tumor growth in cSCC by regulating cyclin B, D and E expression, and also by promoting invasion [ 69 ].…”
Section: Cancer-testis Antigens Are Widely Expressed In Keratinocyte ...mentioning
confidence: 99%
“…Immunostaining for MAGE-A4 was strongest in the basal layer of the epidermis in all four tumor types [ 66 ]. Chen et al also reported that high MAGE-A4 expression was correlated with poorly differentiated cSCCs with PNI [ 69 ].…”
Section: Cancer-testis Antigens Are Widely Expressed In Keratinocyte ...mentioning
confidence: 99%